Analisis Kemampuan Pemandu Wisata dalam Komunikasi Bahasa Inggris kepada Wisatawan di Taman Mini Indonesia Indah, Jakarta - Herienda, Florensia; Adriani, Hanni; Nofiyanti, Fifi; Pradhipta, RMW Agie; Maharani, Mira (Jurnal Ilmiah Pariwisata, 2024)
This research aims to analyze the communication skills of tour guides at Taman Mini Indonesia Indah (TMII), especially in interacting with foreign tourists. The background is the importance of effective communication in increasing tourist satisfaction, especially in the context of globalization. The research methods used include surveys, semi-structured interviews, and observation of guide interactions with tourists. The results showed that guides with more experience had better communication skills, both verbal and non-verbal. Feedback from tourists indicated that interactive and informative communication was highly valued, although some guides still needed to improve their confidence and clarity of explanations. The discussion revealed that effective communication strategies, such as a personal approach and use of body language, can help guides overcome challenges in interactions. The research conclusions emphasize the need for further training of guides in communication aspects, especially English and interpersonal skills. Suggestions for TMII managers include providing regular training for guides and creating an environment that supports positive interactions between guides and tourists, in order to improve the overall quality of the tourist experience. Keywords: communication, tour guide, tourist satisfaction, interaction